Relationship of the Level of Participation of the Elderly in Social Activities with Mental Health in the Community - Zakiyah; Rahmawati Shoufiah (CV. Get Press Indonesia, 2025)
The elderly are an age group that is prone to experiencing a decline in mental health due to various factors such as loneliness, social isolation, and a decrease in social roles in society. One protective factor that is believed to strengthen the mental health of the elderly is involvement in social activities. Objective: This study aims to determine the relationship between the level of participation of the elderly in social activities with their mental health in the community. Methode: this study uses quantitative methods with a correlational approach. The Data were collected through questionnaires to 100 elderly people in RW III anduring selected purposively. The level of social participation was measured based on the frequency and type of social activities followed, while mental health was measured using the WHO-5 Well-Being Index mental health scale. Results: the results of the analysis using the Pearson test showed a significant positive relationship (r = 0.62, p < 0.01) between the level of participation in social activities and the mental health of the elderly. Implications: the implications of these results suggest that increased social participation may be an effective strategy in supporting the mental well-being of the elderly. Therefore, it is important for the government and society to create inclusive social activity programs for the elderly. Conclusion: active participation in social activities has an important role in maintaining and improving the mental health of the elderly in the community.